Usefulness of multidetector CT angiography for anomalous origin of coronary artery - Ishisone, Takenori (BMJ Publishing Group, 2014)
A 17-year-old man underwent clinical evaluation of exercise-induced syncope. Routine exercise stress test did not show any myocardial ischaemic changes or arrhythmias on the ECG recording. However, multidetector CT (MDCT) angiography of the coronary arteries revealed an abnormal origin of the left coronary artery from the right coronary sinus. The participants’ symptoms were diagnosed as cardiogenic syncope possibly due to transient stenosis of the left main coronary artery caught between the functionally distended aortic root and the pulmonary trunk during exercise. After successful patch coronary angioplasty, his symptoms disappeared completely even during a similar degree of strenuous exercise. It is important for clinicians not to overlook possible coronary artery anomalies during management of patients with exercise-induced syncope. MDCT coronary angiography may be a useful and non-invasive tool to establish diagnosis and a surgical approach to rectify congenital coronary artery anomalies.